ZnS Cu-doped quantum dots - Żółczyk, Paulina; Miller, Ewa; Przybyt, Małgorzata (Biotechnology and Food Science, 2014)
The paper presents a survey of literature on the structure and optical properties of ZnS and copper ion-doped ZnS quantum dots. The effect of other metal dopants on the spectral properties of ZnS:Cu quantum dots was also considered. The influence of such parameters as dopant concentration, temperature of the synthesis and compounds which form or modify the additional layer on dots on spectral properties of the quantum dots was described. Examples of application of ZnS:Cu quantum dots are also given.